Churchill and his airmen - Orange, Vincent (Grub Street, 2013)
Winston Churchill probably had more impact on 20th Century British military history than any other person and especially during World War II. With his expert eye, respected historian and professor, Vincent Orange, has carefully studied and evaluated every detail of Churchill's relationships with his closest officers to produce a masterful analysis of a neglected subject.